Malnutrition among High School Tribal Children in Selected Blocks of Chhattisgarh - Atkuri, Ramani; Sardana, Arvind (JOURNAL OF INDIAN EDUCATION, 2018)
This study grew out of new curricular exercises for social science in Chhattisgarh. At a workshop for tribal schools, the teachers were introduced to the idea of nutrition, measurement of Body Mass Index (BMI) and how it is linked to understanding food security. The training emphasised how this could be used in their own schools. The collation and analysis of data from these sample schools located across tribal blocks led to surprising results. What is clearly evident from the data about the children’s heights and weights is that the students of the government tribal schools in Classes IX and X are significantly malnourished. While overall one in four (27 per cent) students is undernourished, boys are more undernourished as compared to girls. Among boys, 39 per cent are undernourished, as compared to 15.7 per cent among girls. Further investigations indicate the evidence of skipping meals and hidden hunger at home. While evidence should be collected on a larger scale, there is an urgent need to introduce Midday Meal (MDM) for high schools in Chhattisgarh, similar to the efforts in some other states.